2015
DOI: 10.1016/s1470-2045(15)00207-7
|View full text |Cite
|
Sign up to set email alerts
|

Combination of hyper-CVAD with ponatinib as first-line therapy for patients with Philadelphia chromosome-positive acute lymphoblastic leukaemia: a single-centre, phase 2 study

Abstract: Background The combination of chemotherapy with a tyrosine kinase inhibitor (TKI) is effective in the treatment of Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL). Ponatinib is a more potent BCR-ABL1 inhibitor and selectively suppresses the resistant T315I clones. We examined the efficacy and safety of combining chemotherapy with ponatinib for patients with Ph+ ALL in this ongoing Phase II prospective trial. Methods Adult patients with newly diagnosed Ph+ ALL and good performance and organ statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
197
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 247 publications
(202 citation statements)
references
References 29 publications
4
197
0
1
Order By: Relevance
“…We continue, therefore, to support a strategy that allows a CHR to be obtained in virtually all patients, including the elderly, based on this chemotherapy-free approach. Furthermore, our study confirms the importance of MRD, the negativity of which should be a major objective in this disease: a higher rate of MRD negativity is likely to be achieved with the inclusion of 2 nd -and, more likely, 3 rd -generation TKI such as ponatinib, which have been proven to have a greater debulking effect, 9,14,16,55 and might possibly be more active in patients with the BCR-ABL p210 form, given the lower MRD clearance observed in this subgroup of patients. As far as ponatinib is concerned, a recent study from the MDACC 55 on 37 patients has indeed shown that its use as upfront therapy, combined with chemotherapy, is able to induce extremely promising results with 2-year event-free survival (EFS) and OS of 81% and 80%, respectively, although 6 toxic deaths were recorded.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…We continue, therefore, to support a strategy that allows a CHR to be obtained in virtually all patients, including the elderly, based on this chemotherapy-free approach. Furthermore, our study confirms the importance of MRD, the negativity of which should be a major objective in this disease: a higher rate of MRD negativity is likely to be achieved with the inclusion of 2 nd -and, more likely, 3 rd -generation TKI such as ponatinib, which have been proven to have a greater debulking effect, 9,14,16,55 and might possibly be more active in patients with the BCR-ABL p210 form, given the lower MRD clearance observed in this subgroup of patients. As far as ponatinib is concerned, a recent study from the MDACC 55 on 37 patients has indeed shown that its use as upfront therapy, combined with chemotherapy, is able to induce extremely promising results with 2-year event-free survival (EFS) and OS of 81% and 80%, respectively, although 6 toxic deaths were recorded.…”
supporting
confidence: 73%
“…As far as ponatinib is concerned, a recent study from the MDACC 55 on 37 patients has indeed shown that its use as upfront therapy, combined with chemotherapy, is able to induce extremely promising results with 2-year event-free survival (EFS) and OS of 81% and 80%, respectively, although 6 toxic deaths were recorded. 55 Other strategies, based on the use of monoclonal antibodies or other immunologic approaches, need to be tested with the goal of offering an overall chemotherapy-free approach that might eradicate/control residual leukemic clones. This is particularly challenging for the elderly/less fit patients, particularly as the prevalence of Ph + ALL cases increases with age.…”
mentioning
confidence: 99%
“…This is an important limitation of our indirect comparison, because treatment paradigms may have changed over time. For instance, recently, ponatinib in combination with chemotherapies demonstrated a significant improvement in 24‐month event‐free OS (up to 81% in patients with Ph+ ALL) 14. Longer follow‐up also may help us understand differences in OS between the intervention groups 15.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] The TKI was continued indefinitely as maintenance therapy. CR was achieved in 196 patients (97%), of whom 122 had MRD assessment for BCR-ABL1 by quantitative polymerase chain reaction at both CR and 3 months, as previously described.…”
Section: Study Design Patientsmentioning
confidence: 99%